Den bildade musikern - Karl Valentin - Ohström, Eva (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2009)
In this article I introduce new material from the Valentin Family Archive at the Royal Library in Stockholm, trying to explain Karl Valentin's strong commitment in general education. Karl Valentin was born into a prosperous family in Gothenburg, and between 1879 and 1885 he studied at the Conservatory of Music in Leipzig, a school well known for its ideal of humanistic general education. The Leipziger bourgeoisie made the well educated artist and the well educated middle class citizen their ideals. I have studied Valentin's activities in Stockholm through saved concert programs from 1901 to 1917. The programs indicate that the folk concerts started with lectures about the music of the evening. During these years, the musical life in Stockholm radically changed and there was an ever increasing number of public concerts. Valentin's folk concerts and lectures were of great importance for the development of a musically educated bourgeoisie in Stockholm.